Exploring the faint young Sun problem and the possible climates of the Archean Earth with a 3‐D GCM. Issue 18 (19th September 2013) - Charnay, B.; Forget, F.; Wordsworth, R.; Leconte, J.; Millour, E.; Codron, F.; Spiga, A.
<x xml:space="preserve">Abstract</x> [1] Different solutions have been proposed to solve the "faint young Sun problem, " defined by the fact that the Earth was not fully frozen during the Archean despite the fainter Sun. Most previous studies were performed with simple 1‐D radiative convective models and did not account well for the clouds and ice‐albedo feedback or the atmospheric and oceanic transport of energy. We apply a global climate model (GCM) to test the different solutions to the faint young Sun problem. We explore the effect of greenhouse gases (CO2 and CH4), atmospheric pressure, cloud droplet size, land distribution, and Earth's rotation rate. We show that neglecting organic haze, 100 mbar of CO2 with 2 mbar of CH4 at 3.8 Ga and 10 mbar of CO2 with 2 mbar of CH4 at 2.5 Ga allow a temperate climate (mean surface temperature between 10°C and 20°C). Such amounts of greenhouse gases remain consistent with the geological data. Removing continents produces a warming lower than +4°C. The effect of rotation rate is even more limited. Larger droplets (radii of 17 μm versus 12 μm) and a doubling of the atmospheric pressure produce a similar warming of around +7°C. In our model, ice‐free water belts can be maintained up to 25°N/S with less than 1 mbar of CO2 and no methane. An interesting cloud feedback appears above cold oceans, stopping the glaciation. Such a resistance against full glaciation tends to strongly mitigate the faint young Sun problem.